Avascular necrosis of the first metatarsal head in adolescence: A case report - Valentina Luppi; Marco Corradin; Roberto Schiavon; Silvia Pierantoni; Andrea Micaglio (PAGEPress Publications, 2022)
Avascular necrosis (AVN) of the first metatarsal (MTT) head is an uncommon condition and it occurs most often as a complication after capital osteotomy in correction of hallux valgus deformity. Idiopathic osteonecrosis of the first MTT head in adolescent are rare and treatment is challenging (1,2). Many conditions have been proposed as predisposing factors of AVN, including trauma, hemoglobinopathies such as sickle-cell disease, steroid therapy, Cushing's disease, alcoholism, Gaucher's disease, Caisson's disease, and irradiation (3,4). However, etiology remains elusive. We described a case of an idiopathic AVN of the 1st MTT in adolescent treated by dorsal closing-wedge osteotomy, which to the authors' knowledge has not been described before.